Collection development strategies for audiovisual archives : Malaysia Government Agencies perspectives - Hashim, Nor Azah; Pati Khan, Mazlina binti; Mohd Nordin, Nordiana (Record and Library Journal, 2024)
Background of the study: The necessity for effective audiovisual (AV) record management nowadays is gaining precedence in most agencies, especially the government sector.  Besides that, AV records are also being demanded to be retrieved and analyzed by researchers who come to the National Archives of Malaysia (NAM). Even though, NAM has found that most government agencies which act as depositor to these records are not actively depositing their valuable government AV records. Purpose: This study aims to identify the issues in depositing AV records to the archives repository and to suggest a significant collection management strategy for encouraging government agencies to deposit their valuable government AV records to NAM for future generation references. Method: The qualitative research method has used by contrivance case study approach. five (5) selected government agencies through the interview of five (5) officers who deal with AV records. Findings: The findings of the study have proposed six (6) strategies to be applied by government agencies to overcome the issues. Conclusion: This study is significant to government agencies, for Records Manager and NAM in increasing and enriching valuable AV archives collection as national heritage.